Improving Children's Cognitive Abilities Through Pattern Play Activities Using Simple Media In Class B1 TK Aba Segajih Hargo Tirto Kokap Kulon Progo In 2024 - Purwanto, Purwanto (USN Kolaka, 2024)
Research on cognitive development in early childhood through pattern playing activities with simple media is expected to improve the cognitive abilities of class B1 children at Segajih ABA Kindergarten. In this research using cycle I, there were seven children who could sort patterns correctly and neatly (46.67 %). Meanwhile, for cycle II, 13 children could sort the patterns correctly and neatly, there were 13 children (86.67%), there were two children who did the work but not correctly and neatly (13.33%), and there were none (13.33%) who did not do the task ( 0%). The results from cycle I and cycle II showed a significant increase in the ability of children to sort patterns correctly and neatly, namely from 7 children (46.67%) to 13 children (86.67). The increase is six children or 20%.